If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + -5x = -18 Solving -3 + -5x = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -5x = -18 + 3 Combine like terms: -3 + 3 = 0 0 + -5x = -18 + 3 -5x = -18 + 3 Combine like terms: -18 + 3 = -15 -5x = -15 Divide each side by '-5'. x = 3 Simplifying x = 3
| x^4+4x^3(-8x^2)+2=0 | | .5(4x+13)+.5= | | Log(3)(x+1)-log(3)x=2 | | t+9=-5 | | 32r^2-50=0 | | 7/x+5-1/x-3=5/3 | | -2-a=-2 | | r+6=6 | | x^4+4x^3-8x^2+2=0 | | .5(2x+4)+9= | | 1/2t^2-16=0 | | -80=-8x | | j-92=-20 | | 6x+3+2x-9x+10x=6+7+4x-9 | | 64b^2=4 | | 4y^2+52y+169=0 | | -2-n=-5 | | 1.50/8 | | d-47=42 | | 132=-12r | | 132=12r | | x-33=-52 | | 2*+4=6 | | n-84=16 | | t-33=-51 | | 3x+88=7x+36 | | 7x+30=2x+130 | | x^2+0.75x+0.125=0 | | 9(x+1)+5(x+1)=5x-5 | | 2.8/4.8=7/x | | 10+5x^2+3x^4=0 | | 5(2x-1)-4(5x-2)=19-2(x+2) |